Characteristics of Marshall Asbuton (Ac-Wc) Premixed with Asphalt Pen 60/70 (AC-WC) on the Duri – Kandis Road Preservation Project - Sp. Palas - Siak II (Pekanbaru) - Islah, Mhd; Adeswastoto, Hanantatur; Sari, Resy Kumala (Journal of Engineering Science and Technology Management, 2023)
The development of development in the industrial world does not escape the use of building materials, one of which is asphalt, which is often used in road construction. Asbuton is one of Indonesia's natural resources whose quality cannot be doubted. One of the asbuton technologies that is widely used is pre-mixed asbuton. Pre-mixed asphalt is one type of modified asphalt used in Indonesia. Pre-mixed Asbuton is processed and mixed with Asphalt Pen 60/70 in a factory that meets certain requirements, so it is equivalent to Modified Asphalt. This research aims to obtain a comparison of the characteristic values of Premixed Asbuton (AC-WC) with Pen 60/70 Oil Asphalt (AC-WC). The method used is experimental by carrying out laboratory tests. The test results for Premixed Asbuton (AC-WC) stability were 1,239.2 and Flow 3.82. Meanwhile, Asphalt Pen 60/70 (AC-WC) Stability is 1,051.4 and Flow 3.17